2020
DOI: 10.3390/nano10071411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Interband Transitions in Gold and Silver on the Dynamics of Propagating and Localized Surface Plasmons

Abstract: Understanding and modeling of a surface-plasmon phenomenon on lossy metals interfaces based on simplified models of dielectric function lead to problems when confronted with reality. For a realistic description of lossy metals, such as gold and silver, in the optical range of the electromagnetic spectrum and in the adjacent spectral ranges it is necessary to account not only for ohmic losses but also for the radiative losses resulting from the frequency-dependent interband transitions. We give a detailed analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 92 publications
(176 reference statements)
1
53
0
1
Order By: Relevance
“…Particularly, metallic nanoparticles NPs attracted substantial interest due to their Localized Surface Plasmon Resonance (LSPR). LSPR properties are very promising to enhance the photocatalytic activities in semiconductors, metal-organic framework (MOF), 2D materials, metals, and perovskites [9][10][11][12][13][14][15][16][17]. Recently, different studies have been reported on the importance of plasmonic metallic nanostructures on the engineering of their properties, e.g., the charge transfer, solar absorption, surface chemistry, stability, selectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, metallic nanoparticles NPs attracted substantial interest due to their Localized Surface Plasmon Resonance (LSPR). LSPR properties are very promising to enhance the photocatalytic activities in semiconductors, metal-organic framework (MOF), 2D materials, metals, and perovskites [9][10][11][12][13][14][15][16][17]. Recently, different studies have been reported on the importance of plasmonic metallic nanostructures on the engineering of their properties, e.g., the charge transfer, solar absorption, surface chemistry, stability, selectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Pure metallic NPs are the most used nanomaterials as plasmonic amplifiers due to the high rate of reproducibility and durability of, i.e., Au. Unfortunately, some have limited surface chemistry such as Ag that degrades due to unstable chemical composition, high cost and are deficient optical absorbers as catalysts [13,34]. By coupling a catalytic material as a protective self-assembled monolayer to the nanoplasmonic NPs, the efficiency of plasmonic NPs is improved by tuning the plasmon resonance higher/lower wavelength therefore expanding the absorption response frequency of NPs [13,31,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, refractive index plasmonic sensors based on surface plasmon polaritons (SPPs) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] have attracted fascinated attention of the experts of biological and chemical detecting since the benefits of nano-size and conquering the diffraction limit [ 8 , 9 , 10 , 11 ]. SPPs are arisen from the free electrons on the surface of metals and are firmly confined to metal-dielectric interfaces [ 12 , 13 ]. One such example is a sensor based on the surface plasmon resonance (SPR) [ 14 , 15 , 16 , 17 ], a nanometer-sized component that depends on the ultra-high sensitivity of SPPs to the environmental media [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PQS operation has attracted much attention from researchers because of the inherent compactness, simplicity, and low cost of their cavities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In recent years, the emergence of low-dimensional nanomaterials with saturable absorption characteristics has become one of the major driving factors of PQS operation [ 20 , 21 , 22 ]. Noble metal nanomaterials have attracted wide interest as a result of their relevance to localized surface plasmon resonance (LSPR).…”
Section: Introductionmentioning
confidence: 99%